Prevalence and Clinical Characteristics of Calciphylaxis in Chinese Hemodialysis Patients - Liu, Yuqiu; Yang, Canlin; Yang, Xin; Xie, Xiaotong; Liu, Hong; Zhang, Liuping; Ye, Jianming; Jiang, Dongsheng; Zhang, Xiaoliang; Liu, Bicheng (Frontiers in Medicine, 2022)
Background: Calciphylaxis is a grievous life-threatening vascular disease that commonly affects dialysis population. This is the first epidemiological survey of calciphylaxis initiated in China. Methods: In the cross-sectional survey, a stratified sampling method was used to select 24 dialysis centers in Jiangsu Province. The participants were all adult patients in each center who had been on hemodialysis for more than 6 months. Calciphylaxis patients were uniformly diagnosed based on characteristic skin lesions and histopathological features. Results: A total of 3867 hemodialysis patients (average age of 55.33±13.89 years; 61.81% of males) were included. 48 cases were diagnosed with calciphylaxis, and prevalence was 1.24%. Among calciphylaxis patients, 33 cases were male, and the average age and median dialysis duration were 53.85±15.17 years and 84.00(48.00, 138.75) months, respectively. Skin biopsy was performed in 70.83% of calciphylaxis patients, and positive rate was 64.71%. Meanwhile, the positive rate of bone scintigraphy in the diagnosis of calciphylaxis was 62.5%. The prevalence of hyperparathyroidism in case group was as high as 72.92% with longer duration, and 42.86% had undergone parathyroidectomy. Multivariate analysis indicated that increased BMI, prolonged dialysis duration, warfarin therapy, hyperparathyroidism, diabetes, tumors, low serum albumin and high serum alkaline phosphatase levels were high-risk factors for calciphylaxis. Conclusions: The prevalence of calciphylaxis in Chinese hemodialysis patients was 1.24% according to regional epidemiological survey, but its actual prevalence would be presumably far beyond present data. It’s urgent to improve clinical understanding of calciphylaxis, and multifaceted diagnostic methods should be applied for early screening.